Advancements in Carbon Capture Technologies - Bhatnagar, Anvi (My University, 2024)
The accumulation of greenhouse gases, particularly carbon dioxide (CO₂), is a signifi-cant driver of global climate change, resulting in severe environmental consequences such as global warming, extreme weather events, and ecosystem degradation. Address-ing this critical issue, the present study investigates cutting-edge carbon capture tech-nologies aimed at reducing CO₂ emissions and aligning with international climate goals, including those outlined in the Paris Agreement. This research provides a comprehensive analysis of various carbon capture technolo-gies, including Direct Air Capture (DAC), pre-combustion, post-combustion, and oxy-fuel combustion methods. Case studies, such as the Mitsubishi Heavy Industries’ Hy-drogen Gas Turbine and the HyNet Project in the UK, highlight real-world applications and underscore the transformative potential of integrating these technologies into existing energy and industrial systems. For instance, DAC offers substantial flexibility in placement and significant CO₂ removal capacity but is hindered by high energy de-mands and current cost barriers. Conversely, innovations in hydrogen-powered tur-bines and hybrid systems demonstrate the feasibility of transitioning traditional fossil-fuel systems to cleaner energy alternatives. The study emphasizes the critical need for continuous innovation, increased invest-ment, and supportive policies to enhance the economic and technical feasibility of carbon capture technologies. By integrating technological advancements with real-world applications, Ultimately, it contributes to the global effort to achieve net-zero emissions, ensuring a sustainable future in the face of escalating climate challenges.
Keywords: carbon dioxide; emissions; climate changes; carbon capture and storage; environmental technology; greenhouse gases; renewable energy sources; environmental effects; energy technology; fi=Energiatekniikka|en=Energy Technology|; Master´s Programme in Smart Energy